Potassium Use Efficiency of Natural Zeolite-Based Potassium Fertilizer in Oil Palm Seedlings (Elaeis guineensis Jacq.) Using Peat Soil Media - Anwar, Syaiful; Murtilaksono, Kukuh; Nugroho, Budi; Rahutomo, Suroso (Jurnal Penelitian Kelapa Sawit, 2023)
Potassium is the most needed macronutrient for oil palm. However, the efficiency of potassium fertilization on peatlands is low due to leaching. One of the exertions to improve this fertilization's efficiency is peat soil amelioration and engineering fertilizer technology so that plants can absorb nutrients more efficiently. This study aims to evaluate the effectiveness of zeka fertilizer, a modified potassium fertilizer made from natural zeolite, on oil palm seedlings in peat soil. The study used a completely randomized design with five treatments and three replications. The treatments were (1) K0 = Control/no fertilizer; (2) K1 = standard fertilizer, namely: urea + TSP + KCl + dolomite; (3) K2 = urea + TSP + zeka-1 + dolomite; K3 = urea + TSP + zeka-2 + dolomite; K4 = urea + TSP + zeka-3 + dolomite. The results proved that, in general, zeka fertilizer (K2, K3, and K4) produced better seedling growth and nutrient use efficiency than the standard fertilization treatment of oil palm seedlings (K1). The best treatment (K3) resulted in the highest growth and nutrient efficiency. K3 treatment resulted in seedling height and stem diameter by 7.7% and 9.2%, respectively, compared to K1. Furthermore, the dry biomass of the shoot and roots produced by the K3 treatment was 39.2% and 33.9% higher, respectively, than that produced by the K1 treatment. The agronomic efficiency, Apparent Recovery efficiency, Physiological efficiency, and Partial Factor Productivity of K3 treatment were 59.91%, 33.23%, 18.57%, and 39.16% higher than K1, respectively.